Natural hydrocolloids for nanotechnological applications in foods - Vicente, A. A. (2011)
Nanotechnological solutions, e.g. through the development of edible nanofilms and nanocoatings, in particular under the form of edible nanolaminates [1, 2]. The base materials are essentially the same: polysaccharides, proteins and/or lipids. Polysaccharide- and proteinbased films/coatings provide good barriers to O2 and CO2, but are very permeable to water vapor; in turn, lipid-based films/coatings provide excellent barriers to water vapor but have a limited resistance to other gases and have low mechanical resistance. The use of successive nano-layers of materials will provide a) better physical stability in aggressive environments; b) better chemical stability to active compounds which may be incorporated into these structures; and c) improved control of the release rates of such compounds. Applications of this technology are envisaged e.g. for the enhancement of food safety, for the encapsulation of functional food ingredients [3], and in systems providing the integration of sensing, localization, reporting and remote control of food products. At the current state of knowledge, many of these applications may be difficult to adopt commercially because they are either too expensive or difficult to implement at an industrial scale. This means that there is much room for research and development in this area. A final word of caution is needed: in many cases the effects of nanotechnological systems in the human body are still unclear. This means that using nanotechnological applications in foods must be justified essentially by their advantages, which must be clearly perceived by the consumer. Not doing so will undermine consumers trust on this emerging technology, eventually hindering its success in future applications.